Effectiveness of peer education based on social cognitive theory in preventing anemia among adolescent girls at the State Senior High School 1 Kebomas Gresik - Eka Srirahayu Ariestiningsih; Dwi Faqihatus Syarifah Has; Bhagaskoro Ardhianto Kurniawan; Luluk Yuliati Yuliati; Hilda Putri Laurita; Maghfiratun Nisa Arifani (AcTion: Aceh Nutrition Journal, 2025)
Anemia remains a significant global public health issue, particularly among adolescent girls. In Indonesia, 48,9% of adolescent girls were anemic in 2018, and East Java reported a prevalence of 42% in 2020. Contributing factors include poor nutrition, unhealthy dietary habits, and low awareness of anemia prevention. This study aimed to evaluate the effectiveness of peer education in enhancing adolescents’ knowledge and awareness of anemia prevention and analyze its behavioral impact based on Social Cognitive Theory (SCT). A mixed-method approach with an explanatory sequential design was employed. Quantitative data were collected from 110 students (grades X and XI) at the State Senior High School 1 Kebomas Gresik between March and April 2025, using pre- and post-tests (20 items) and a validated SCT-based questionnaire (15 items, r = 0,847). Qualitative insights were obtained through in-depth interviews with peer educators, guided by five key SCT-based questions. Statistical analyses included paired t-tests or Wilcoxon tests for knowledge improvement and SEM-PLS for behavioral correlations. Post-intervention results showed a significant increase in knowledge (mean score: 75,06 to 95,28) with a moderate yet significant correlation (r= 0,494; p= 0,000). In conclusion, peer education grounded in SCT proved effective in promoting knowledge transfer and behavioral change, supporting its use as a health education strategy for adolescents.